NEW PRODUCT LAUCH CONSIGNMENT PROGRAM INFORMATION SYSTEM AT PT. INDOMARCO ADI PRIMA - Khairul Syahputra; Zulfahmi Syahputra; Sri Wahyuni (INFOKUM, 2022)
Consignment is a program where producers or product producers carry out goods storage to retail stores for resale. PT. Indomarco Adi Prima is a company that has a consignment program for its products. This study builds an information system for recording consignment data in the form of snack food products that are deposited in stores. This system records the order and the number of items deposited along with the expiration date. This information system facilitates the marketing of PT. Indomarco Adi Prima is monitoring the goods for further checking. By using this system, the recording of the consignment program will run accordingly